Peran Pendidikan Dalam Membangun Karakter Bangsa Yang Bermoral - Inanna, Inanna (Universitas Negeri Makassar, 2018)
This paper is a scientific idea that aims to give an idea of the importance of building the character of moral human resources, through the internalization of positive values in the implementation of education. This is one way to be able to overcome various issues, especially moral decadence among young people. The method used is literature review. In general, the values that need to be developed and internalized in the implementation of education in Indonesia, among others, religious, mutual cooperation, togetherness, humility, refinement, hospitality, tolerance, so that the unity and unity of the nation can be realized